2012
DOI: 10.1111/j.1399-6576.2012.02765.x
|View full text |Cite
|
Sign up to set email alerts
|

LMA ProSealTM vs. i‐GelTM in ventilated children: A randomised, crossover study using the size 2 mask

Abstract: We conclude that oropharyngeal leak pressure and fiberoptic position of the airway tube are similar for the size 2 LMA ProSeal(TM) and i-Gel(TM) in non-paralysed ventilated children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 11 publications
6
39
1
Order By: Relevance
“…The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance. The 10-min airway leak pressures are similar to the airway leak pressures demonstrated in recent reports on the LMA ProSeal [2,17,18] and igel [1,15,16] in children.…”
Section: Discussionsupporting
confidence: 67%
“…The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance. The 10-min airway leak pressures are similar to the airway leak pressures demonstrated in recent reports on the LMA ProSeal [2,17,18] and igel [1,15,16] in children.…”
Section: Discussionsupporting
confidence: 67%
“…The mean oropharyngeal leak pressure with the i-gel was between 21 and 28 cmH 2 O. Gasteiger et al [12] and Fukuhara et al [13] found no significant differences between the devices. The largest trial in this group was by Tokgoz et al [14] and included i-gel sizes 1-2.5.…”
Section: Study Selection Bias Information Bias Measurement Errors Conmentioning
confidence: 99%
“…In the studies by Goyal et al [6] and [10] Unclear Unclear High* Unclear Kus et al [11] Unclear Unclear High* Unclear Gasteiger et al [12] Low Unclear High* Low † Goyal et al [6] Low Unclear High* Unclear Fukuhara et al [13] Low Unclear High* Unclear Das et al [7] Low Unclear High* Unclear Das et al [8] Low Unclear High* Unclear Lee et al [22] Unclear Unclear High* Unclear Theiler et al [18] Low Low High* Low † Tokgoz et al [14] Low Unclear High* Unclear Lee et al [16] Unclear Unclear High* Unclear Kim et al [17] Low Low High* Unclear Mitra et al [15] Low Unclear High* Unclear *Not possible to blind researchers to airway device used. †Intention to treat analysis stated.…”
Section: Oropharyngeal Leak Pressurementioning
confidence: 99%
“…The modified cuff design of the PLMA may allow for more consistent administration of positive pressure ventilation (PPV) with potentially higher leak pressures [13]. Several studies have examined this device compared with other supralaryngeal devices such as the i-gel in relaxed pediatric patients in the setting of PCV [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…PSV increases inspired tidal volumes (TVs) and may ultimately reduce the work of breathing in smaller children [1,6]. In some settings, where patient-initiated breaths have ceased all together or neuromuscular blocking drugs have been used, controlled ventilation using pressure control (PCV) may be necessary [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%